2008
DOI: 10.1091/mbc.e08-02-0231
|View full text |Cite
|
Sign up to set email alerts
|

The Scaffold Protein POSH Regulates Axon Outgrowth

Abstract: How scaffold proteins integrate signaling pathways with cytoskeletal components to drive axon outgrowth is not well understood. We report here that the multidomain scaffold protein Plenty of SH3s (POSH) regulates axon outgrowth. Reduction of POSH function by RNA interference (RNAi) enhances axon outgrowth in differentiating mouse primary cortical neurons and in neurons derived from mouse P19 cells, suggesting POSH negatively regulates axon outgrowth. Complementation analysis reveals a requirement for the third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(71 citation statements)
references
References 39 publications
(91 reference statements)
4
67
0
Order By: Relevance
“…Recent studies confirmed that the scaffold proteins of SH3s (POSH), actin-myosin regulatory protein SHROOM3, and Rho Kinase (ROCK) have been involved in the downstream signaling pathways of PirB to participate in the inhibition of neuronal outgrowth (Dickson et al, 2010;Taylor et al, 2008). The important downstream molecules in the PirB pathway were also observed in the present study.…”
Section: Expression Of Posh Shroom3 Rock1 and Rock2 In Tle Patientssupporting
confidence: 88%
See 2 more Smart Citations
“…Recent studies confirmed that the scaffold proteins of SH3s (POSH), actin-myosin regulatory protein SHROOM3, and Rho Kinase (ROCK) have been involved in the downstream signaling pathways of PirB to participate in the inhibition of neuronal outgrowth (Dickson et al, 2010;Taylor et al, 2008). The important downstream molecules in the PirB pathway were also observed in the present study.…”
Section: Expression Of Posh Shroom3 Rock1 and Rock2 In Tle Patientssupporting
confidence: 88%
“…Experiments in vitro indicate that MAG restricts axon growth by binding to PirB, and this process is accompanied by the activation of SHP1/ 2 (Fujita et al, 2011). Moreover, in the cortical neurons, downregulation of PirB expression using RNA interference led to increased outgrowth of processes (Taylor et al, 2008). To our knowledge, axonal sprouting has been documented in the hippocampal formation, amygdala and temporal cortices in epileptic human and animal brains (Tolner et al, 2003;Yan et al, 2012).…”
Section: Lilrb2/pirb In Tlementioning
confidence: 86%
See 1 more Smart Citation
“…Shroom3 is a multi-domain protein that can interact with and/or recruit components of the cytoskeletal machinery, including actin and Rho kinase (Rock1/2) (Hildebrand and Soriano, 1999;Nishimura and Takeichi, 2008;Taylor et al, 2008). Shroom3 also possesses a proline-rich sequence (FPn) that matches the consensus binding sequence of the Mena/Vasp family of proteins and raises the possibility that there might be an interaction between the FPn-binding (EVH1) domain of Mena/Vasp and Shroom3 (Fig.…”
Section: The Shroom3 Fpn Domain Mediates Apical Constrictionmentioning
confidence: 99%
“…It has been shown that AB elongation of pseudostratified epithelial cells in the developing neural tube depends on Shroom3, a PDZ binding domaincontaining protein that localizes to the apical adherens junction (Haigo et al, 2003;Hildebrand, 2005;Hildebrand and Soriano, 1999). Interestingly, Shroom3 also controls apical constriction, another attribute shared by most pseudostratified epithelia (Haigo et al, 2003;Hildebrand, 2005;Lee et al, 2009;Lee et al, 2007;Nishimura and Takeichi, 2008;Taylor et al, 2008).…”
Section: Introductionmentioning
confidence: 99%